Covering the Building of a Kingdom: The Saudi Arabian Authority in The London Times and The New York Times, 1901–1932. (September 2015) - Alrebh, Abdullah F.
Abstract The orientalist literature subjected the Middle East in an exotic way — mostly as an "Arabian Nights" society ruled by traditional sultans and/or tribal chiefs — rather than modern governance structure's "bureaucracy." The presumption within postcolonial scholarship has been that this perception influenced the policy landscape in the United States and Europe, especially the media depictions of the oriental leaders and leadership. The paper empirically tests this hypothesis through content analysis using Weber's categorization of leadership of two newspapers of record — The New York Times in the United States and The London Times in the United Kingdom — during the period of state building in Saudi Arabia (1901–1932). I find that rather than depicting the Saudi leadership as "backward, " these newspapers in particular, tend to overstate the development of the Saudi state during this period. As Weber is best known for his three types of authority, it benefits the discipline to see how the interpretive communities of Western journalists operationalized "authority" in terms of politics and religion of Saudi Arabia as this monarchy emerged.